The multicopy gene Sly represses the sex chromosomes in the male mouse germline after meiosis. - Julie Cocquet; Peter J I Ellis; Yasuhiro Yamauchi; Shantha K Mahadevaiah; Nabeel A Affara; Monika A Ward; Paul S Burgoyne (PLoS Biology)
Studies of mice with Y chromosome long arm deficiencies suggest that the male-specific region (MSYq) encodes information required for sperm differentiation and postmeiotic sex chromatin repression (PSCR). Several genes have been identified on MSYq, but because they are present in more than 40 copies each, their functions cannot be investigated using traditional gene targeting. Here, we generate transgenic mice producing small interfering RNAs that specifically target the transcripts of the MSYq-encoded multicopy gene Sly (Sycp3-like Y-linked). Microarray analyses performed on these Sly-deficient males and on MSYq-deficient males show a remarkable up-regulation of sex chromosome genes in spermatids. SLY protein colocalizes with the X and Y chromatin in spermatids of normal males, and Sly deficiency leads to defective repressive marks on the sex chromatin, such as reduced levels of the heterochromatin protein CBX1 and of histone H3 methylated at lysine 9. Sly-deficient mice, just like MSYq-deficient mice, have severe impairment of sperm differentiation and are near sterile. We propose that their spermiogenesis phenotype is a consequence of the change in spermatid gene expression following Sly deficiency. To our knowledge, this is the first successful targeted disruption of the function of a multicopy gene (or of any Y gene). It shows that SLY has a predominant role in PSCR, either via direct interaction with the spermatid sex chromatin or via interaction with sex chromatin protein partners. Sly deficiency is the major underlying cause of the spectrum of anomalies identified 17 y ago in MSYq-deficient males. Our results also suggest that the expansion of sex-linked spermatid-expressed genes in mouse is a consequence of the enhancement of PSCR that accompanies Sly amplification.